Conflict-Based Search for Multi-Robot Motion Planning with Kinodynamic Constraints - Kottinger, Justin; Almagor, Shaull; Lahijanian, Morteza (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2022)
Multi-robot motion planning (MRMP) is the fundamental problem of finding non-colliding trajectories for multiple robots acting in an environment, under kinodynamic constraints. Due to its complexity, existing algorithms are either incomplete, or utilize simplifying assumptions. This work introduces Kinodynamic Conflict-Based Search (K-CBS), a decentralized MRMP algorithm that is general, scalable, and probabilistically complete. The algorithm takes inspiration from successful solutions to the discrete analogue of MRMP over finite graphs, known as Multi-Agent Path Finding (MAPF). Specifically, we adapt ideas from Conflict-Based Search (CBS)-a popular decentralized MAPF algorithm-to the MRMP setting. The novelty of our approach is that we work directly in the continuous domain, without discretization. In particular, the kinodynamic constraints are treated natively. K-CBS plans for each robot individually using a low-level planner and grows a conflict tree to resolve collisions between robots by defining constraints. The low-level planner can be any sampling-based, tree-search algorithm for kinodynamic robots, thus lifting existing planners for single robots to the multi-robot setting. We show that K-CBS inherits the (probabilistic) completeness of the low-level planner. We illustrate the generality and performance of K-CBS in several case studies and benchmarks.